Microstructure And Kinetic Growth Of Aluminide Coating On 304 Stainless Steel By Slurry Aluminizing - Tan, Siew Min (Universiti Sains Malaysia, 2022)
Aluminide coating by slurry aluminizing has gained interest by industry to improve the corrosion resistance of structural materials operating in harsh environments. However, depletion of aluminium from the coating into the substrate and mismatch in coefficient thermal expansion (CTE) became obstacles in developing a good protective aluminide coating. Austenitic stainless steel 304 was chosen as the substate due to the smaller CTE mismatch between substrate and the coating. Furthermore, Al2O3 was added to the slurry composition as an aluminizing agent to slow the inward diffusion of aluminium into the substrate. The aim of this project is to study the effect of heat treatment temperature and time on the aluminide coating formation with the present of alumina. The slurry coated sample was heat treated at various temperatures (600, 630, 650, 680, and 700°C) and times (4, 6, 8 and 10 hours). At 600 and 630°C, a thin layer of aluminide was formed due to the low temperature which not able to induce the solid-state diffusion. Based on EDX, XRD, and nano hardness analysis, FeAl3 formed in the outer layer and FeAl phase developed in the interdiffusion zone (IDZ). The aluminide coating and FeAl thickness increase as heat treatment temperature and time increases. According to the Arrhenius equation, the activation energy for FeAl3 and FeAl phase was 214.630 kJ/mol, while the activation energy for FeAl phase was 343.153 kJ/mol. Heat-treated samples at 700°C for 10 hours had better corrosion resistance due to thicker coating thickness. Aluminide coating developed on austenitic stainless steel 304 yields promising results and has the potential to be used as a protective coating.